Digital games to develop english basic vocabulary for sixth graders students of Unidad Educativa José Pedro Varela, La Libertad, Santa Elena province, 2018 - 2019 - Minaya Solórzano, Josselyn Katherine (2020)
Nowadays, teaching English as a foreign or second language demands the implementation of strategies that allow students to learn in a more didactic and dynamic way. The use of technology and games during the teaching process represents an alternative in which students are able to acquire new knowledge in a relaxing environment. Thus, the digital games have assumed a very relevant role in the educational lives of children and teenagers. Games may be used for teaching, practicing, or even evaluating the diverse students’ English skills; listening, speaking, reading, writing; vocabulary and grammar as well. For this work, digital games were implemented for developing and improving the low knowledge level of English vocabulary of students of sixth grade from Unidad Educativa “José Pedro Varela” located in La Libertad during the 2018 – 2019 academic period which represents the basis for the acquisition of English and its four main skills and be able to communicate with English speakers from the community and abroad. The quantitative research method was applied in this investigation, a survey was also implement in order to collect information about the teaching and learning process on students.